ASSESSMENT OF GYPSUM QUALITY ON SETTING TIME ABOUT CEMENT PRODUCTION AND OTHER INDUSTRIAL APPLICATIONS IN NAFADA L.GA. GOMBE STATE, NORTHEASTERN NIGERIA - Ashaka, U.I; Abatcha, B.A.; Muhammad, M.A. (FUDMA Journal of Earth and Environmental Sciences, 2025)
The quality of gypsum is a critical factor in cement production, particularly in terms of its impact on setting time and the overall performance of the cement. This assessment examines the dual role of gypsum as both a retarder and a strength enhancer in Portland cement. Gypsum, primarily composed of calcium sulfate dihydrate (CaSO₄·2H₂O), regulates the hydration process by controlling the reaction of tricalcium aluminate (C₃A), thus preventing flash setting and allowing for extended workability. The study highlights that optimal gypsum content typically ranges from 5% to 6%, which has been shown to enhance compressive and flexural strength while maintaining desirable setting times. Impurities in gypsum can adversely affect these properties, leading to inconsistent performance and potential structural issues. The findings underscore the importance of high-quality gypsum in achieving superior cement characteristics, emphasizing that excessive amounts or low-purity gypsum can lead to detrimental expansion and reduced strength. Overall, this research provides valuable insights into optimizing gypsum quality for improved cement production, with implications for both industry practices and future studies aimed at enhancing material performance. The purity of gypsum is crucial; lower purity levels (below 65%) can negatively impact the quality of cement. High-quality gypsum contributes positively to both the setting time and strength characteristics of cement, whereas impurities may compromise its performance.